Laminate and method for producing a laminate

By designing a separate structure in the laminated material, applying tension with the recording layer and the cover layer causes cohesion failure, the problem of uneven adhesion in the prior art is solved, and the tamper-proof of anti-counterfeiting elements is improved and peeling force enhances anti-counterfeiting protection.

CN119136992APending Publication Date: 2024-12-13OVD KINEGRAM AG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380036243.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-25
Filing Date
2023-04-19
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the bonding method, the uneven adhesion of the existing laminated materials due to different material characteristics is easily separated or tampered by the counterfeiter, and it is difficult to detect tamper attempts.

Method used

A laminated material including a recording layer, a transparent cover layer and an anti-counterfeiting element is designed, which has a disengagement layer, a replication layer, a reflective layer and an adhesive layer, which is separated by the recording layer and the covering layer with tension applied to the recording layer, Cohesion failure is achieved, thereby increasing peeling force and difficult to reuse.

Benefits of technology

Through the cohesive failure of the adhesive layer, the undetectable separation difficulty of the anti-counterfeiting components is increased, the peeling force is improved, the detectability of tampering is reduced, and the anti-counterfeiting protection is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136992A_ABST
    Figure CN119136992A_ABST
Patent Text Reader

Abstract

The present invention relates to a laminate (1) comprising a security element (20) laminated between a recording layer (11) and a cover layer (12), in which an adhesive layer (25) is adhered to the recording layer (11) and a release layer (21) is adhered to the cover layer (12), or the adhesive layer (25) is adhered to the cover layer (12) and the release layer (21) is adhered to the recording layer (11), and a method for manufacturing the laminate (1), and the laminate (1) is designed in such a way that the adhesive layer (25) of the security element (20) can be separated by the tension exerted on the security element (20) by the recording layer (11) and the cover layer (12).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a laminate and a method for producing a laminate.

[0002] As is well known, security element is encapsulated between two layers connected to each other in a material bonding mode in a laminate such as a security document, and as a result, the security element is completely surrounded by the two layers of the security document. Material bonding has achieved high adhesion and protects the security element from damage and tampering. However, due to the different material properties of the layer of the security element and the adjacent layer of the security document combined in a material bonding mode, different boundary surfaces with different adhesions, particularly reduced adhesion, are formed at the boundary surface of the security element. If the security element has different adhesions at its boundary surface with the layer combined in a material bonding mode, the counterfeiter can remove the security element by separating or peeling off the layer of the security document in a targeted manner, or add false information in the security document and seal it again.

[0003] The object of the present invention is therefore to provide a laminated material, in particular a security document, having improved protection against manipulation and counterfeiting, and to provide a method for producing such a laminated material.

[0004] This object is achieved by a laminated material, in particular a security document, according to claim 1. The laminated material, in particular the security document, comprises a recording layer, a transparent cover layer and a security element laminated between the recording layer and the cover layer. The security element comprises a release layer, a replication layer, a reflection layer and an adhesive layer, wherein the replication layer has a relief surface arranged on its side facing away from the release layer, and the reflection layer is arranged on the relief surface. The adhesive layer forms the side of the security element facing away from the release layer, wherein

[0005] a) the adhesive layer adheres to the recording layer and the release layer adheres to the cover layer, or the adhesive layer adheres to the cover layer and the release layer adheres to the recording layer;

[0006] also,

[0007] b) The laminate is designed in such a way that the adhesive layer of the security element can be separated by the tension exerted on the security element by the recording layer and the cover layer.

[0008] The object is also achieved by a method according to claim 31. In a method for producing a laminated material, in particular a security document, preferably as claimed in any one of claims 1 to 30, the following steps are performed, in particular in a specified order:

[0009] - preparing a recording layer;

[0010] - preparing a transparent cover layer;

[0011] - preparing a security element, in particular for a laminate according to the invention, preferably for a laminate according to any one of claims 1 to 30. The security element comprises a release layer, a replication layer having a relief surface arranged on its side facing away from the release layer, a reflection layer arranged on the relief surface, and an adhesive layer, the replication layer having a relief surface arranged on its side facing away from the release layer, the reflection layer being arranged on the relief surface, the adhesive layer forming the side of the security element facing away from the release layer. The security element is attached to the cover layer or the recording layer via the adhesive layer or is already attached to the cover layer or the recording layer via the adhesive layer;

[0012] - laminating the security element between the recording layer and the cover layer such that:

[0013] a) the adhesive layer adheres to the recording layer and the release layer adheres to the cover layer, or the adhesive layer adheres to the cover layer and the release layer adheres to the recording layer; and

[0014] b) The adhesive layer of the security element can be separated by the tension exerted on the security element by the recording layer and the cover layer.

[0015] According to the present invention, the adhesive layer of the laminate and the laminate that can be obtained by the method of the present invention can be separated by the cohesive failure caused by the tension of the recording layer and the cover layer on the security element. Within the meaning of the present invention, the existence of the adhesive layer that can be separated can be determined specifically by the peel test described previously. Cohesive failure is particularly the adhesive fracture of the adhesive itself, preferably, wherein the adhesive force of the adhesive on the material surface is greater than the internal strength of the adhesive. In the case where cohesive failure occurs in the adhesive layer, particularly the adhesive layer is separated into two partial layers, wherein the partial layers of the adhesive layer separated from each other in each case continue to adhere to the direct adjacent layer of the adjacent adhesive layer. In particular, these two partial layers are continuous layers in each case, which have been separated from each other by cohesive failure or are separated from each other by cohesive failure, wherein preferably there is pure cohesive failure. During cohesive failure, the extended crack tip may temporarily hit the boundary surface of the layer adjacent to the adhesive layer, but will not extend along it in the case of separation, for example, the adhesive layer exists in the form of an incompletely continuous partial layer after separation in each case, and / or, the adhesive layer exists mainly in the form of a continuous partial layer after separation in each case. On the other hand, in the event of adhesion failure, the adhesive layer loosens, particularly at the boundary surface with the directly adjacent adhesive layer and one or more layers adjacent to the adhesive layer, particularly causing the adhesive layer to detach from the boundary surface in a continuous manner or predominantly in a continuous manner due to adhesion failure.

[0016] Due to the presence of a split adhesive layer, the undetectable detachment or reuse of the entire security element becomes more difficult, because when the cover layer is peeled off, due to the separation of the adhesive layer, in particular due to the cohesive failure of the adhesive layer, parts or partial layers of the adhesive layer are also peeled off, so the layer thickness of the security element is reduced, and the plastic deformation of the adhesive layer persists, in particular persists on the surface of the security element. Therefore, tampering attempts are advantageously easier to detect, or only reduce detectability through additional efforts. In addition, studies have shown that an increased peeling-off force, preferably also referred to as peeling force, can be achieved by a split adhesive layer or due to a corresponding predetermined breaking point defined by the adhesive layer, which is necessary in the case of attempting to detach the cover layer or the recording layer from the security element. Therefore, due to the existing adhesive conditions, the delamination of the laminate and the lossless reuse of the security element become more difficult. Therefore, particularly high adhesion can also be achieved at the boundary surface of the adhesive layer and the boundary surface of the detachment layer and the adjacent recording layer or the adjacent covering layer, so that in particular the difference between the adhesion at the two boundary surfaces of the adhesive layer can be adapted, and in particular the difference can be reduced, making the continuous detachment of the layer of the easily controlled security document more difficult.

[0017] In particular, the laminate of the invention is produced by the process of the invention. The process of the invention is therefore preferably carried out to obtain the laminate of the invention.

[0018] Advantageous embodiments of the invention are described in the dependent claims.

[0019] "Adhere" preferably means directly connected. The adhesive layer preferably adheres directly to the recording layer, wherein the release layer adheres directly to the cover layer; or the adhesive layer adheres directly to the cover layer, wherein the release layer adheres directly to the recording layer. In particular, the value of the adhesion of the two layers attached to each other measured according to standard ISO / IEC 10373-1:2006 (E), paragraph 5.3 and / or the following peel test is higher than 1N / 10mm strip width, preferably higher than 1.5N / 10mm strip width, further preferably higher than 3.5N / 10mm strip width. In other embodiments, an intermediate layer can be arranged between the adhesive layer and the recording layer.

[0020] "Layer" refers in particular to an essentially two-dimensional structure. The layer itself can preferably be monolayer or multilayer.

[0021] Laminated material refers in particular to a multilayer structure, wherein at least two layers are connected to each other in a material bonding manner, in particular welding. For example, the laminated material is produced by a laminating method or has been produced by a laminating method. The laminating method can be carried out as further described below. "Laminated" (laminated in) or "laminating in" specifically refers to a material bonding connection, in particular a material bonding connection of a recording layer and a cover layer, preferably having been produced by a laminating method or produced by a laminating method, preferably resulting in the security element being completely surrounded by two layers. Preferably when observed perpendicular to the plane or main surface spanned by the laminated material and / or the security element, the security element has been laminated by welding, and preferably completely around the security element to the recording layer and the cover layer or particularly by welding, and preferably completely around the security element to the recording layer and the cover layer laminated.

[0022] If the "plane" or "major surface" thickness is neglected, the "plane" or "major surface" preferably refers to the surface spanned by the laminate or the security element or one of the layers of the laminate and / or the security element.

[0023] “Transparent” preferably means a transmittance of more than 90%, in particular a transmittance of more than 90% at a wavelength of 380 nm to 780 nm, preferably at a wavelength in the range of wavelengths visible to the human eye.

[0024] “Translucent” preferably means a transmittance of 30% to 90%, in particular a transmittance of 30% to 90% at a wavelength of 380 nm to 780 nm, preferably at a wavelength in the range of wavelengths visible to the human eye.

[0025] "Opaque" preferably means a transmittance of less than 30%. "Transmittance" preferably means the ratio of the amount of light irradiating and / or incident on a medium to the amount of light emerging on the opposite side of the medium, wherein in particular the frequency or wavelength of the light is not changed. The light that is not transmitted is preferably reflected, scattered and / or absorbed by the medium. Thus, in the case of a medium with a transmittance of 0.9 or 90%, for example, 90% of the irradiated light is perceptible on the opposite side of the medium.

[0026] When considering the transmittance of a layer, in particular reflections from boundary surfaces of the layer are not taken into account.

[0027] The security element can provide an optically variable effect. The optically variable effect can be selected from the following items individually or in combination in particular: the color change depending on the viewing angle, the contrast change depending on the viewing angle, the theme change depending on the viewing angle, holographic reproduction, movie reproduction. The viewing angle of the security element can be changed by the observer, particularly by tilting, rotating and / or bending changes. The security element is preferably formed as a transfer layer of a transfer film or is formed as a transfer layer of a transfer film. One or more security elements may have been laminated in a security document having an adhesive layer that adheres to a recording layer and a release layer that adheres to a cover layer or will be laminated in a security document having an adhesive layer that adheres to a recording layer and a release layer that adheres to a cover layer, and one or more other security elements have been laminated in a security document having an adhesive layer that adheres to a cover layer and a release layer that adheres to a recording layer or will be laminated in a security document having an adhesive layer that adheres to a cover layer and a release layer that adheres to a recording layer.

[0028] The recording layer and / or the cover layer preferably contain polycarbonate or consist of polycarbonate. It is particularly advantageous if the recording layer and the cover layer contain polycarbonate or consist of polycarbonate, in particular have been or are connected to one another in a materially bonded manner by lamination, in particular welded together. During lamination, a particularly stable connection can be achieved. The cover layer preferably has a layer thickness of 25 μm to 250 μm and / or the layer thickness of the cover layer is 1.25 to 250 relative to the layer thickness of the adhesive layer and / or the sum of the thickness of the adhesive layer and the thickness of the cover layer is 26 μm to 270 μm.

[0029] Besides polycarbonate, for example the cover layer and / or the recording layer can also contain dyes, in particular color pigments and / or effect coatings, for example optically variable pigments (OVI) and / or metal pigments.

[0030] Preferably, the thickness of the recording layer is 25 μm to 250 μm. The recording layer can be processed by laser in particular, or processed by laser. The recording layer preferably also contains other substances, such as in particular dopants. The ability of the recording layer to absorb energy can be increased by dopants. The material of the dopant is in particular selected from one or more of the following materials: chromium, erbium, neodymium, praseodymium, titanium, ytterbium. Therefore, the information item has been inscribed in the recording layer or is inscribed in the recording layer, for example by a laser, preferably by a YAG laser, preferably by a Nd:YAG laser (abbreviation of neodymium-doped yttrium aluminum garnet laser). The emission wavelength of the YAG laser is preferably 1064 nm. The cover layer is preferably transparent to a wavelength of 1064 nm and / or to the wavelength of the laser. Therefore, the recording layer can be processed by laser, in particular by laser processing through the cover layer, so as to write the information item in the recording layer. The anti-counterfeiting element preferably overlaps with these written information items, thereby increasing the anti-counterfeiting protection of the laminated material, in particular the anti-counterfeiting document.

[0031] Adhesive layer can be connected to adhere to cover layer or recording layer by material bonding (particularly adhesive). Release layer is preferably connected to adhere to cover layer or recording layer by welding, particularly when there is no intermediate adhesive connection. Particularly, cover layer and recording layer, preferably also release layer form integral body (monolithic body). Therefore, the connection of security element on adhesive layer and release layer is preferably based on different physical principles, which preferably makes the release of security element on release layer side very complicated or even impossible. Adhesive layer is preferably connected to adhere to reflective layer and / or to adhere to replica layer by material bonding. Reflective layer is particularly connected to adhere to replica layer by material bonding.

[0032] The material bonding connection of the recording layer and the cover layer, for example in the form of polycarbonate layers, in particular polycarbonate layers consisting of almost 100% polycarbonate, is advantageously achieved by welding together by lamination, which is considered to be an ideal interconnection and thus offers a counterfeiter little possibility to separate the individual layers from each other without destroying them. For example, separation of the layers cannot be easily achieved by applying tension on the boundary surfaces. However, the security element laminated therein acts in particular as a foreign body in the structure, i.e. the adhesion to the adjacent cover and recording layers, in particular to the adjacent polycarbonate layers, is significantly reduced compared to direct adhesion between the cover and recording layers. In order to extract the security element from the laminate, the counterfeiter could cut into the polycarbonate layer before the security element is separated at the edge and then try to peel off one of the layers. This procedure was reproduced by the following test and can be made more difficult by the predetermined breaking point provided by the adhesive layer for cohesive failure and more preferably by the selected geometry and material parameters, for example by increasing the peeling force.

[0033] The measurement of the peel force can be carried out in particular as described below, preferably by a peel test on the laminate. The peel force is also particularly referred to as peel strength, peel-off force, pull-off force or adhesion. The peel force can be measured in particular by a peel test according to ISO / IEC 10373-1:2006 (E), paragraph 5.3 and / or the peel test described below.

[0034] In the peel test, the optionally preconditioned laminate (preferably in card form) is specifically cut into test strips 10 mm wide.

[0035] For example, one or all layers on one side of the security element are then removed, thus, for example, a corresponding portion of the recording layer or the cover layer, preferably a length of 5 mm to 10 mm. Stripping is done with a sharp knife from the core, ie in particular the cover layer from the recording layer or the recording layer from the cover layer. The stripping is conveniently done only partially.

[0036] The torn-off end, in particular the torn-off end of the cover layer, is then preferably fixed to a support of the tensile tester by means of a fixing clip or an adhesive tape. Preferably, a right angle is produced between the torn-off layer fixed to the tensile tester and the untorn layer. In particular, a right angle is produced between the cover layer and the recording layer. The bottom of the laminate, in particular the recording layer, is conveniently optionally fixed to a stabilizing plate.

[0037] During the tensile measurement, the detached film layer can preferably be guided onto a roller. The adhesion (peel strength) is preferably plotted on a diagram and then evaluated, wherein the first 5 mm and the last 5 mm of the measurement are preferably not taken into account. For example, the result is given in N / 10 mm.

[0038] Measurements can also be carried out in locations without security elements, for example in order to measure the adhesion between cover layer and recording layer.

[0039] In particular, it has proven to be advantageous to reduce the thickness of the adhesive layer in direct proportion to the thickness of the stabilizing layer which is preferably arranged between the adhesive layer and the replication layer, in particular to ensure cohesive failure in the case of adhesion of the adhesive layer to the recording layer.

[0040] Advantageously, a peel force equal to or greater than 3.5 N / 10 mm strip width is already provided or will be provided in the laminate for detaching the cover layer from the security element.

[0041] Adhesive layer is preferably used for bonding the transfer layer carrying one or more security elements of the present invention to substrate during application, that is, when security element is applied to cover layer or recording layer as substrate, especially so. This can be an adhesive layer activated by heat and pressure. This adhesive layer activated by heat and pressure can have thermoplasticity especially, or can also be crosslinked by the effect of heat, thereby can prevent new thermal activation. This adhesive layer as mixed layer also may have thermoplastic part and crosslinking composition. Usually use hot stamping to activate, its shape defines the region to be transferred.

[0042] Alternatively, the transfer can be achieved by so-called cold transfer. The adhesive layer is preferably printed on the transfer layer of the transfer film or on the cover layer or recording layer, and then the cover layer or recording layer is brought into contact with the transfer layer and the adhesive layer is cured, in particular, the security element is formed by the transfer layer and the printed adhesive layer. Curing is especially achieved by UV irradiation. The adhesive layer can be composed of a plurality of different layers and include, for example, one or more adhesion promoter layers to ensure in particular the bonding of the adhesive layer to the reflective layer or the optionally present stabilizing layer.

[0043] The adhesive force of the adhesive layer to its directly adjacent layer consisting of a cover layer or a recording layer is advantageously higher than the cohesive force of the adhesive layer. The adhesive force within the adhesive layer, in particular the cohesive force of the adhesive layer, is preferably lower than the adhesive force between the security element and the recording layer, and also lower than the adhesive force between the security element and the cover layer.

[0044] It is particularly advantageous if the adhesive layer has the lowest yield point, in particular the lowest upper yield point and / or the lowest elastic modulus, of the layers of the security element, recording layer and / or cover layer. The smallest force among the cohesive forces and adhesive forces in the security element or in the laminate with the security element is preferably the cohesive force of the adhesive layer.

[0045] The adhesive layer may also comprise an ductile layer or consist of an ductile layer, in particular wherein the ductile layer is that layer of the security element which has the greatest elongation at break compared to the other layers of the security element.

[0046] Thus, the adhesive layer may have or consist of a ductile layer, wherein the ductile layer is a layer that can be separated by cohesive failure. In particular, compared to a brittle adhesive layer, the ductile layer advantageously promotes cohesive failure or makes adhesive failure more difficult, in particular increases the peel force.

[0047] Particularly, laminated material can be designed to, during peel test and / or attempt to break away from cover layer and / or recording layer from laminated material, pure cohesive failure occurs, or adhesive layer is separated from the layer consisting of cover layer or recording layer in one or more partial surfaces of boundary surface with directly adjacent. This is especially true under the situation of partial adhesion failure. However, the surface area of ​​these one or more partial surfaces is preferably smaller than the remaining surface of boundary surface, preferably does not show the separation of adhesive layer and adjacent layer. The remaining surface of boundary surface has the residual of adhesive layer especially, because there is cohesive failure there. Laminated material is preferably designed to make one or more partial surfaces occupy small surface area, make peeling force be at least 3.5N / 10mm, and described peeling force is preferably measured with peel test. To this, for example, the layer thickness of adhesive layer can be adjusted accordingly and / or can use optional stabilizing layer.

[0048] Preferably, the remaining surface covers at least 50%, at least 80%, preferably at least 90% of the surface area of ​​the boundary surface, and / or one or more partial areas cover less than 50%, preferably less than 20%, preferably less than 10% of the surface area of ​​the boundary surface.

[0049] Here, the observation is carried out in particular along a line perpendicular to the plane spanned by the boundary surface. In general, high peel forces can also be advantageously ensured in the presence of irregularities in the laminate, which can lead to local peaks of tensile stress and thus to local adhesive failures. In an advantageous embodiment, the adhesive layer, in particular the stretching layer, comprises a material with an elastic modulus (elastic modulus = modulus of elasticity) of 20 MPa to 300 MPa, preferably 50 MPa to 200 MPa, preferably 75 MPa to 150 MPa. The modulus of elasticity is determined in each case in particular in accordance with DIN EN ISO 527-3:2003-07 ("Plastics-Determination of tensile properties-Part 3: Test conditions for films and sheets-issue date: 2003-07"), preferably at room temperature (25° C.). The tensile modulus of elasticity is determined here by means of a tensile testing machine, for example from the ZwickRoell Group of Ulm, Germany. GmbH & Co. KG, Ulm, DE.), determined on film test strips. The width of the film strip is preferably 15 mm + / - 0.1 mm, the length of the film strip is preferably 100 mm + / - 0.5 mm, or for film materials with high elongation, the length of the film strip is preferably 50 mm + / - 0.5 mm. For a film length of 100 mm, the test speed is 10 mm / min + / - 1 mm / min, or for a film length of 50 mm, the test speed is 5 mm / min + / - 1 mm / min.

[0050] The adhesive layer is in particular arranged over the entire surface and continuously in the security element. This makes it possible to prevent stress differences that favour adhesive failure, in particular when peeling off the cover layer.

[0051] In particular, the adhesive layer contains a thermoplastic or a polymer to be crosslinked or a crosslinked polymer, in particular polymethyl methacrylate and / or polybutyl methacrylate.

[0052] "Cross-linking" refers in particular to a chemical reaction, preferably a polymerization reaction, by which macromolecules, in particular polymers, are linked to form a three-dimensional network.

[0053] The adhesive layer is preferably already prepared on the basis of the following materials selected from polymethyl methacrylate and polybutyl methacrylate, alone or in combination, or prepared on the basis of the following materials selected from polymethyl methacrylate and polybutyl methacrylate, alone or in combination. The adhesive layer may also contain one or more additives selected from fillers, for example TiO2, BaSO4 or silica, alone or in combination.

[0054] The glass transition temperature Tg of the adhesive layer is preferably 20° C. to 50° C. Furthermore, it is preferred that the melting temperature Tm of the adhesive layer is 40° C. to 150° C. In particular, the molar mass of the adhesive layer is 100 kg / mol to 350 kg / mol.

[0055] In particular, the thickness of the adhesive layer is 0.2 μm to 20 μm, preferably 0.2 μm to 10 μm. Particularly preferably, the thickness of the adhesive layer is 3.5 μm to 20 μm, further preferably 3.5 μm to 10 μm and / or preferably 4 μm to 20 μm, further preferably 4 μm to 10 μm and / or 6 μm to 20 μm, in particular 6 μm to 10 μm.

[0056] The adhesive layer is preferably transparent or translucent. The adhesive layer may have a milky optical impression. Cohesive failures in the adhesive layer can advantageously be optically detected particularly easily by the translucent and / or milky adhesive layer. For this, for example, TiO2 may be contained in the adhesive layer.

[0057] Before application, the adhesive layer may have a slightly rough surface. The surface roughness is preferably 0.4 μm to 2.0 μm, in particular 0.6 μm to 1.0 μm. The measurements required for this are preferably performed with a microscope (in particular Keyence VK-X3000) and the software required for it (possibly VK Analyzer).

[0058] The thickness of the release layer is 0.2 μm to 10 μm, preferably 0.2 μm to 5 μm. The release layer comprises or consists of a material selected from the following materials alone or in combination: thermoplastics, thermoplastic elastomers, crosslinked polymers, UV crosslinked polymers, isocyanates, additives, catalysts, release agents. UV crosslinkable refers in particular to UV curable, and UV crosslinked refers in particular to UV curable.

[0059] The release layer is conveniently transparent. Preferably, before lamination of the security element, the release layer has a smooth surface. In particular, before lamination, the release layer has a low surface roughness, preferably an R3z value of less than 2 μm, preferably less than 0.5 μm.

[0060] It has been shown that, when laminated, the adhesion of the release layer to the adjacent cover layer or adjacent recording layer can be achieved in a manner that is stronger than the adhesion within the adhesive layer, in particular the cohesion of the adhesive layer. In addition, the adhesion of the release layer to the adjacent cover layer or adjacent recording layer can be greater than the adhesion between the adhesive layer and the cover layer or the recording layer adjacent to the adhesive layer. Thus, the separation behavior of the laminate can advantageously be set in a targeted manner by the adhesive layer.

[0061] The reflective layer advantageously consists of a material whose refractive index differs from that of the replica layer by at least 0.2. The reflective layer preferably comprises or consists of a metal layer or a high refractive index layer (=HRI layer, layer with high refractive index) or a combination thereof. Typical materials for HRI layers are for example ZnS and / or TiO2. The high refractive index layer may comprise a material selected from SiO2, alone or in combination. x ,MgO,TiO x , Al2O3, ZnO, ZnS, or selected from SiO x ,MgO,TiO x , Al2O3, ZnO, ZnS. The variable x is preferably in the range of 0 to 3, so x=0, 1, 2, 3. The reflective layer may include or consist of the following metals, alone or in combination: chromium, aluminum, gold, copper, tin, indium, silver and alloys of one or more of the above metals. The reflective layer may also preferably contain one or more metal oxides selected from aluminum oxide, chromium oxide, silicon oxide, indium tin oxide, titanium oxide and combinations thereof. For wavelengths of 420nm to 780nm, the reflective layer preferably has a refractive index greater than 1.9. The layer thickness of the reflective layer is 40nm to 200nm, preferably 40nm to 100nm. The layer thickness is preferably related to the layer of the reflective layer. In the case of a multilayer reflective layer, one or more layers may in particular have a specified layer thickness.

[0062] The reflective layer is usually deposited by vapor deposition or sputtering in a vacuum. The reflective layer can also be applied or designed only partially and / or have different thicknesses in partial areas.

[0063] On the side of the adhesive layer facing the replication layer and the reflective layer, the security element preferably has a stabilizing layer. By means of the stabilizing layer, it is achieved in particular that a laminate can be formed such that a cohesive failure can be provided in the adhesive layer or a cohesive failure becomes more likely when the cover layer is peeled off, for example in the case of relatively thin adhesive layers (which themselves are still prone to adhesive failure). The stabilizing layer largely maintains the brightness of the optical effect during lamination, advantageously also plays a protective role during lamination and prevents warping of the security element, in particular of the transfer layer with the security element.

[0064] The thickness of the stabilizing layer is preferably 0.5 μm to 20 μm, preferably 1 μm to 10 μm. In particular, if the adhesive layer is adhered to the recording layer, the thickness of the stabilizing layer is preferably 1 μm to 10 μm and / or the thickness of the stabilizing layer together with the thickness of the adhesive layer is at least 1 μm and / or the thickness of the stabilizing layer together with the thickness of the adhesive layer is at most 40 μm and / or the thickness of the stabilizing layer is 0.1 to 20 times the thickness of the adhesive layer. In particular, it has proven to be advantageous for the ratio of the thickness of the adhesive layer to the thickness of the stabilizing layer to be in the range of 0.4 to 4.

[0065] It has proven to be advantageous for the stabilization layer to have or to consist of a layer consisting of a material having a modulus of elasticity of 500 MPa to 1500 MPa.

[0066] The stabilizing layer comprises in particular a material selected from the group consisting of thermoplastics, thermoplastic elastomers, crosslinked polymers, UV crosslinked polymers, isocyanates, additives, catalysts, release agents, or consists of a material selected from the group consisting of thermoplastics, thermoplastic elastomers, crosslinked polymers, UV crosslinked polymers, isocyanates, additives, catalysts, release agents, etc. The stabilizing layer can be formed from a varnish crosslinkable by radiation or from a chemically reactive varnish (e.g. epoxy resin).

[0067] The stabilizing layer preferably has a brittle behavior. During a separation attempt or during a measurement of the elastic modulus of a tensile specimen of the laminate, the stabilizing layer advantageously deforms elastically.

[0068] The stabilizing layer is preferably transparent, in particular clear and transparent. The stabilizing layer preferably has a smooth surface. The stabilizing layer can also consist of multiple layers, for example including an adhesion promoter layer for bonding to the reflective layer.

[0069] One or more other layers realizing other functions can be located between the release layer and the replication layer. For example, a protective layer arranged between the release layer and the replication layer can be provided. When the anti-counterfeiting element is laminated between the recording layer and the cover layer, in particular when the recording layer and the cover layer comprise polycarbonate or are composed of polycarbonate, this particularly realizes a stable mechanical action that prevents degradation. For this reason, this protective layer is already heat-stable or preferably heat-stable, for example cross-linked by radiation or chemical reaction and heat-stabilized. The protective layer preferably comprises a material selected from the following substances alone or in combination or preferably consists of a material selected from the following substances alone or in combination: thermoplastics, thermoplastic elastomers, cross-linked polymers, or UV cross-linked polymers, isocyanates, additives, catalysts, release agents.

[0070] For laminating the security element, a lamination method is or preferably is performed, preferably by means of a roll laminator or a lifting and lowering press.

[0071] In the case of a roller laminator, the recording layer, the cover layer and the security element disposed between the two layers can be inserted between at least two heated rollers, for example. In the case of a lift press, the recording layer, the cover layer and the security element disposed between the two layers can be inserted between heating plates, for example.

[0072] The lamination has preferably been carried out by applying a pressure of 10 N / cm2 to the recording layer, the cover layer and / or the security element. 2 Up to 400N / cm 2 , preferably 40N / cm 2 Up to 200N / cm2 or by applying a pressure of 10 N / cm2 on the recording layer, cover layer and / or security element. 2 Up to 400N / cm 2 , preferably 40N / cm 2 Up to 200N / cm 2 The lamination may be achieved by a temperature of more than 150° C., preferably 160° C. to 210° C. or by a temperature of more than 150° C., preferably 160° C. to 210° C., which acts on the recording layer, the covering layer and / or the security element from a heat source, in particular from one or more heating rollers or one or more heating plates. The lamination is preferably carried out by a contact time of 1 minute or more and 30 minutes or less between the heat source and the recording layer and / or the covering layer or by a contact time of 1 minute or more and 30 minutes or less between the heat source and the recording layer and / or the covering layer. The contact of the heat source with the recording layer and the covering layer is preferably achieved directly or indirectly through other layers. The above-mentioned settings are preferably used for covering layers and recording layers composed of or containing polycarbonate. For other materials, such as polyvinyl chloride, different temperature and pressure settings can be used that are matched to the material to be processed.

[0073] Before or in order to prepare a cover layer or a recording layer provided with a security element, the following steps may be performed in the specified order:

[0074] - preparing a transfer film having a carrier layer and a transfer layer, wherein the transfer layer has the security element and the release layer is arranged on a side of the security element facing the carrier layer;

[0075] - Applying the security element to the recording layer or the covering layer.

[0076] Mechanically stable, and therefore in particular self-supporting, carrier films are conveniently used as carrier layers. Typically, the carrier layer comprises or consists of polyester, preferably polyethylene terephthalate (abbreviation: PET) or polyethylene naphthalate (abbreviation: PEN). The thickness of the carrier layer is preferably 5 to 150 μm, preferably 5 to 50 μm, further preferably 10 to 25 μm. The carrier layer is preferably transparent.

[0077] The application of the security element is preferably carried out by the following steps in the specified order:

[0078] - applying an adhesive layer to the recording layer or the cover layer;

[0079] - Peeling the carrier layer off the transfer layer, with the result that the security element remains on the recording layer or cover layer.

[0080] The transfer layer can be transferred completely or partially, for example by a predefined pattern transfer by an embossing die or an embossing roller. Alternatively, an adhesive printed on a region, in particular a patterned adhesive, can transfer the transfer layer within the region, with the result that the security element is formed by the printed adhesive and the transfer layer transferred within the region. The adhesive layer of the security element then preferably comprises or consists of the printed adhesive layer.

[0081] During application, the release layer conveniently ensures that the composite layer of the transfer layer can be detached from the carrier layer. In particular, when the security element is laminated, the release layer can surprisingly ensure that good adhesion to an adjacent cover layer or recording layer is achieved, in particular if it comprises or consists of polycarbonate. The release layer thus fulfils a dual function in particular, since it ensures, on the one hand, improved detachment during production and, on the other hand, improved adhesion in the end product.

[0082] One or more wax layers can be arranged between the release layer and the carrier layer. In particular, the separation of the transfer layer and the carrier can be improved by one or more (preferably thin) wax layers. In various cases, the thickness of the wax layer is preferably 1nm to 50nm. Preferably, one or more wax layers are removed before the anti-counterfeiting element is laminated. In particular, the firm bonding of the release layer and the recording layer or the cover layer can be achieved thus.

[0083] The application of the adhesive layer is preferably carried out by hot stamping or by hot stamping. Hot stamping can be carried out at a temperature of 80° C. to 300° C., preferably 100° C. to 240° C., particularly preferably 100° C. to 180° C. Hot stamping is preferably carried out at a pressure of 10 N / cm 2 Up to 10,000N / cm 2 , preferably 100N / cm 2 Up to 5000N / cm 2 The punching pressure is 10N / cm 2 Up to 10,000N / cm 2 , preferably 100N / cm 2 Up to 5000N / cm 2 The hot stamping is preferably carried out with a stamping time of 0.01 s to 2 s, preferably 0.01 s to 1 s or with a stamping time of 0.01 s to 2 s, preferably 0.01 s to 1 s.

[0084] The relief surface of the replication layer preferably forms an optically active structure. An “optically active structure” is in particular a structure selected from the group consisting of the following, alone or in combination: a diffractive surface relief, a holographic surface relief, a first-order diffraction grating, a zero-order diffraction structure, a blazed grating, an achromatic surface relief, a surface relief in the form of a lens and / or a lens grid, a micromirror arrangement, a microprism, a microlens, a microfacet, a free surface, a mirror, a matte structure (in particular an isotropic or anisotropic matte structure).

[0085] The replication layer can also comprise or consist of a thermoplastic or a crosslinked polymer, preferably a UV crosslinked polymer. Prior to replication, the replication layer preferably has a smooth surface. The thickness of the replication layer is in particular 0.2 μm to 20 μm, preferably 0.2 μm to 10 μm.

[0086] The relief surface has been molded into the replication layer or into the replication layer by replication molding. The molding can be achieved in a thermoplastic manner by the following process: the surface is structured into a corresponding negative relief by a tool with an optically active structure, which is preferably carried out under pressure and temperature. The replication layer can also be formed by a polymerizable varnish or a polymerized varnish, which is preferably composed of monomers and oligomers, which are polymerized or have been polymerized after or during the introduction into the relief surface. This polymerization can be achieved by UV irradiation or electron beam irradiation. The replication layer can also represent a hybrid form that has been thermoplastically deformed and then cured or is being thermoplastically deformed and then cured. The replication layer preferably comprises a material selected from the following substances alone or in combination or is preferably composed of a material selected from the following substances alone or in combination: thermoplastic plastics, crosslinked polymers, or UV crosslinked polymers, isocyanates, additives, catalysts, release agents.

[0087] In the following, the invention is described by way of example with reference to a number of embodiment examples with the aid of the accompanying drawings. They are shown in:

[0088] Figure 1a , 1b , 1c and 1d schematically show cross sections of laminated materials,

[0089] Figure 2a , 2b , 3a and 3b schematically show a method for producing a laminate,

[0090] Figure 4a and 4b Schematic showing the transfer membrane and its production,

[0091] Figure 5 Schematic showing the peel test setup,

[0092] Figure 6Schematic representation of the measured curves for brittle and ductile material failure.

[0093] Figure 1a and 1b The laminated material 1 is shown schematically in cross section in each case. The laminated material 1 is preferably a security document.

[0094] The laminate 1 comprises a recording layer 11, a transparent cover layer 12 and a security element 20. The security element 20 is laminated between the recording layer 11 and the cover layer 12. The security element 20 has a release layer 21, an optional protective layer 22, a replication layer 23 having an embossed surface arranged on its side facing away from the release layer 21, a reflective layer 24 arranged on the embossed surface and an adhesive layer 25.

[0095] The adhesive layer 25 forms the side of the security element 20 facing away from the release layer 21. The laminate 1 is designed so that the adhesive layer 25 of the security element 20 can be separated by the tension exerted on the security element 20 by the recording layer 11 and the cover layer 12.

[0096] Figure 1a The laminate 1 is shown with the adhesive layer 25 adhered to the recording layer 11 , wherein the release layer 21 adheres to the cover layer 12 . Figure 1b The laminate 1 is shown with the adhesive layer 25 adhered to the cover layer 12 , wherein the release layer 21 adheres to the recording layer 11 .

[0097] In the depicted cross-section, the thickness of the layer is indicated in particular by the height and is therefore the dimension in the vertical direction. Viewing in a plane or main surface spanned by the laminate or its layers corresponds, for example, to viewing from above. The laminate 1 and the adhesive layer 25 of the laminate obtained by the process according to the invention can be separated in particular by tension exerted on the security element 20 by the recording layer 11 and the covering layer 12. Based on Figure 5 The presence of a separable adhesive layer 25 or a predetermined breaking point defined by the adhesive layer can be determined, in particular by means of a peel test as described below.

[0098] The connection between the cover layer 12 and the recording layer 11 is not shown. Figure 1a and 1b However, usually, no intermediate space is provided in the laminate 1 between the cover layer 12 and the recording layer 11. The opposing surfaces of the cover layer 12 and the recording layer 11 are fused together, in particular in the region outside the security element 20, such as Figure 1c and Figure 1dAs shown, in particular, this can be achieved by the method described herein. In particular, the covering layer 12 and the recording layer 11 form a monolithic body. "Laminated in" or "laminating in" means that the material bonding connection of the recording layer 11 and the covering layer 12 has been produced by a lamination method or is produced by a lamination method, preferably with the result that the security element 20 is completely surrounded by the two layers 11 and 12. In particular, the security element 20 has been laminated by welding the recording layer 11 and the covering layer 12 or is being laminated by welding the recording layer 11 and the covering layer 12, and in the process preferably completely surrounds the security element 20, preferably when viewed perpendicularly to the plane or main surface spanned by the laminated material 1, as Figure 1a and Figure 1b As shown in the top view.

[0099] The recording layer 11 preferably also contains other substances, such as, in particular, dopants. The ability of the recording layer 11 to absorb energy can be increased by dopants. The material of the dopant is particularly selected from one or more of the following materials: chromium, erbium, neodymium, praseodymium, titanium, ytterbium. Therefore, the information item has been inscribed in the recording layer 11 or is inscribed in the recording layer 11, for example by a laser, preferably by a YAG laser, preferably by a Nd:YAG laser (abbreviation for neodymium-doped yttrium aluminum garnet laser). The emission wavelength of the YAG laser is preferably 1064nm. Therefore, the recording layer 11 can be processed by laser, in particular by laser processing through the cover layer 12, so as to write the information item in the recording layer 11. The anti-counterfeiting element 20 preferably overlaps with these written information items, thereby increasing the anti-counterfeiting protection of the laminated material 1, in particular the anti-counterfeiting document.

[0100] In a preferred embodiment, the recording layer 11 and / or the cover layer 12 contain polycarbonate or consist of polycarbonate. So-called composite laminates are also conceivable, in which the recording layer and / or the cover layer consist of different materials, for example PVC with a PET core. It is particularly advantageous if the recording layer 11 and the cover layer 12 contain polycarbonate or consist of polycarbonate and are already or by lamination connected to one another in a materially bonded manner, in particular welded together. Thus, during lamination, a particularly stable connection can be achieved. The materially bonded connection of the polycarbonate layers, in particular the materially bonded connection consisting of almost 100% polycarbonate, is advantageously achieved by welding together by the lamination process and cannot be separated or can only be separated with difficulty by a counterfeiter. By the following tests, in particular if Figure 5 The test shown reproduces a detachment attempt (in particular with reduced adhesion of the security element 20 ) and can be made more difficult by cohesive failure and correspondingly selected geometry and material parameters, for example by increasing the peel force.

[0101] In reference Figure 1a In the example of the described laminate 1, for example, the following layer thicknesses can be achieved. In this example, the layer thickness of the cover layer 12 is preferably 50 μm to 150 μm. In this example, the thickness of the recording layer 11 is preferably 50 μm to 150 μm. In this example, the thickness of the adhesive layer 25 is preferably 2 μm to 10 μm. In this example, the thickness of the reflective layer 24 is preferably 40 nm to 100 nm. In this example, the thickness of the replication layer 23 is preferably 0.2 μm to 10 μm. In this example, the thickness of the optional protective layer 22 is preferably 1.0 μm to 10.0 μm.

[0102] In reference Figure 1b In the example of the described laminate 1, for example, the following layer thicknesses can be achieved. In this example, the layer thickness of the cover layer 12 is preferably 50 μm to 150 μm. In this example, the thickness of the recording layer 11 is preferably 50 μm to 150 μm. In this example, the thickness of the adhesive layer 25 is preferably 2 μm to 10 μm. In this example, the thickness of the reflective layer 24 is preferably 40 nm to 100 nm. In this example, the thickness of the replication layer 23 is preferably 0.2 μm to 10 μm. In this example, the thickness of the optional protective layer 22 is preferably 0.1 μm to 10 μm.

[0103] The adhesive layer 25 is attached to the Figure 1a The recording layer 11 or Figure 1b The release layer is preferably attached to the cover layer 12 by welding. Figure 1a The cover layer 12 or Figure 1b The recording layer 11 is shown. The adhesive layer preferably adheres to the reflective layer by a material bonding connection and / or to the replication layer 23 by a material bonding connection. The reflective layer adheres to the replication layer 23 in particular by a material bonding connection.

[0104] The adhesive force of the adhesive layer 25 to its directly adjacent layer consisting of the cover layer 12 or the recording layer 11 is advantageously higher than the cohesive force of the adhesive layer 25. The adhesive force within the adhesive layer 25, in particular the cohesive force of the adhesive layer 25, is preferably lower than the adhesive force between the security element 20 and the recording layer 11, and also lower than the adhesive force between the security element 20 and the cover layer 12.

[0105] It is particularly advantageous if the adhesive layer 25 has the lowest yield point, in particular the lowest upper yield point and / or the lowest elastic modulus, among the layers of the security element 20, the recording layer 11 and / or the cover layer 12. Of the cohesive forces and adhesive forces within the security element 20 or within the laminate 1 having the security element 20, the smallest force is preferably the cohesive force of the adhesive layer 25. Figure 1a and 1b As shown, the adhesive layer 25 is arranged in particular over the entire surface and continuously in the security element 20 .

[0106] During application, ie in particular when the security element 20 is applied to the cover layer 12 and / or the recording layer 11 as substrate, the adhesive layer 25 preferably serves to bond the transfer layer of the transfer film, see for example Figure 4a and Figure 4b As shown, the transfer film carries one or more security elements 20 of the present invention. This can be an adhesive layer 25 activated by heat and pressure. For this, hot stamping is usually used for activation, and its shape defines the area to be transferred. Or, transfer can be realized by so-called cold transfer. The printing layer composed of adhesive forms the adhesive layer 25 in the laminate 1 or is contained in the adhesive layer 25, which is preferably printed on the transfer layer of the transfer film, on the cover layer 12 or on the recording layer 11. The cover layer 12 or the recording layer 11 are preferably contacted with the transfer layer subsequently, and the printing layer composed of adhesive is cured, and the security element 20 is formed by the transfer layer and the printed adhesive layer. The adhesive layer 25 can then be composed of a plurality of different layers, and includes, for example, one or more adhesion promoter layers (preferably except the stretching layer), to ensure the bonding of the adhesive layer 25 and the reflective layer 24 or the optionally present stabilizing layer.

[0107] The adhesive layer 25 may also comprise an ductile layer or consist of an ductile layer, in particular wherein the ductile layer is the layer of the security element which has the greatest elongation at break compared to the other layers of the security element.

[0108] Therefore, the adhesive layer 25 can have or consist of a ductile layer, wherein the ductile layer can be separated by cohesive failure. In particular, compared with a brittle adhesive layer, the ductile layer advantageously promotes cohesive failure or makes adhesive failure more difficult. As a result, the peeling force can be increased.

[0109] In an advantageous embodiment, the adhesive layer 25, in particular the stretching layer, comprises or consists of a material having an elastic modulus of 20 MPa to 300 MPa, preferably 50 MPa to 200 MPa, preferably 75 MPa to 150 MPa. The elastic modulus is determined in each case according to DIN EN ISO 527-3: 2003-07 ("Plastics - Determination of tensile properties - Part 3: Test conditions for films and sheets - Issue date: 2003-07 (Plastics - Determination of tensile properties - Part 3: Test conditions for films and sheets - Issue date: 2003-07) date:2003-07)), preferably at room temperature (25°C). Here, the tensile modulus of elasticity is determined on a film test strip by a tensile testing machine (e.g. a tensile testing machine from ZwickRoell GmbH & Co. KG, Ulm, DE., Germany). The width of the film strip is preferably 15 mm + / - 0.1 mm, and in particular for film materials with high elongation, the length of the film strip is preferably 100 mm + / - 0.5 mm or 50 mm + / - 0.5 mm. For a film length of 100 mm, the test speed is 10 mm / min + / - 1 mm / min, or for a film length of 50 mm, the test speed is 5 mm / min + / - 1 mm / min.

[0110] The adhesive layer 25 is preferably already produced on the basis of polymethyl methacrylate or is produced on the basis of polymethyl methacrylate. The adhesive layer 25 may also contain one or more additives selected from fillers, such as TiO2, BaSO4 or silica, either alone or in combination.

[0111] The adhesive layer 25, in particular the spreading layer, may be milky white.

[0112] In particular, the thickness of the adhesive layer 25, in particular the stretching layer, is 0.2 μm to 20 μm, preferably 0.2 μm to 10 μm. The thickness of the adhesive layer is particularly preferably 3.5 μm to 20 μm, further preferably 3.5 μm to 10 μm and / or 4 μm to 20 μm, preferably 4 μm to 10 μm and / or 6 μm to 20 μm, in particular 6 μm to 10 μm. The glass transition temperature Tg of the adhesive layer is preferably 20° C. to 50° C. In addition, the melting temperature Tm of the adhesive layer is preferably 40° C. to 150° C. In particular, the molar mass of the adhesive layer is 100 kg / mol to 350 kg / mol.

[0113] Before being applied to the cover layer 12 or the recording layer 11, the adhesive layer 25 may have a slightly rough surface. The surface roughness is preferably 0.4 μm to 2.0 μm, in particular 0.6 μm to 1.0 μm. The measurement required for this is preferably performed with a microscope (which may be Keyence VK-X3000) and the software required for it (which may be VK Analyzer).

[0114] In particular, the release layer 21 has a thickness of 0.2 μm to 10 μm, preferably 0.2 μm to 5 μm, here for example 4 μm. The release layer 21 may comprise or consist of a thermoplastic, a thermoplastic elastomer or a crosslinked polymer (preferably a UV crosslinked polymer). The release layer 21 comprises or consists of a material selected from the following substances, alone or in combination: thermoplastics, thermoplastic elastomers, crosslinked polymers, or UV crosslinked polymers, isocyanates, additives, catalysts, release agents. The release layer 21 is conveniently transparent. Preferably, before lamination, the release layer 21 has a low surface roughness, in particular an R3z value of less than 2 μm, preferably less than 0.5 μm.

[0115] For example, a reflective layer 24 consisting of aluminum with a layer thickness of 50 nm is used here. The reflective layer 24 can also include or consist of a metal layer or a high refractive index layer (=HRI layer) or a combination thereof. Typical materials for HRI layers are, for example, ZnS and / or TiO2. The high refractive index layer can include a material selected from SiO2, alone or in combination. x ,MgO,TiO x , Al2O3, ZnO, ZnS, or selected from SiO x ,MgO,TiO x , Al2O3, ZnO, ZnS. The variable x is preferably in the range of 0 to 3, so x=0, 1, 2, 3. The reflective layer 24 can include or consist of the following metals alone or in combination: chromium, aluminum, gold, copper, tin, indium, silver and alloys of one or more of the above metals. The reflective layer 24 may also preferably contain one or more metal oxides selected from aluminum oxide, chromium oxide, silicon oxide, indium tin oxide, titanium oxide and combinations thereof. For wavelengths of 420nm to 780nm, the reflective layer 24 preferably has a refractive index greater than 1.9. The layer thickness of the reflective layer 24 can be 40nm to 200nm, preferably 40nm to 100nm, and here is, for example, 50nm. The reflective layer may also be only partially designed and / or have different thicknesses in partial areas.

[0116] On the side of the adhesive layer 25 facing the replication layer 23 and the reflective layer 24 , the security element 20 preferably has a stabilization layer 26 .

[0117] The stabilizing layer 26 advantageously fulfills its protective function during lamination by serving to maintain the brightness of the optical effect during lamination and prevents warping of the security element 20, in particular of the transfer layer with the security element 20. At the same time, by means of the stabilizing layer 26, it is possible in particular to form the laminate 1 so that a predetermined breaking point can be provided by cohesive failure of the adhesive layer 25, or when the cover layer 12 is peeled off, for example in the case of a relatively thin adhesive layer 25 (which itself is still prone to adhesive failure), a cohesive failure becomes more likely.

[0118] The thickness of the stabilizing layer 26 is preferably 0.5 μm to 20 μm, preferably 1 μm to 10 μm. In particular, it is preferred that if the adhesive layer 25 is adhered to the recording layer 11, the thickness of the stabilizing layer 26 is 1 μm to 10 μm, and / or the thickness of the stabilizing layer 26 together with the thickness of the adhesive layer 25 is at least 1 μm and / or the thickness of the stabilizing layer 26 is 0.1 to 20 times the thickness of the adhesive layer 25.

[0119] It has proven to be advantageous if the stabilization layer 26 comprises or consists of a layer consisting of a material having a modulus of elasticity of 500 MPa to 1500 MPa.

[0120] The stabilizing layer 26 comprises or consists of a material selected from the following alone or in combination: thermoplastics, thermoplastic elastomers or crosslinked polymers, or UV crosslinked polymers, isocyanates, additives, catalysts, release agents. The stabilizing layer 26 can be formed from a varnish that can be crosslinked by radiation, or from a chemically reactive varnish (e.g., epoxy resin).

[0121] The stabilization layer 26 preferably has a brittle behavior.

[0122] The stabilization layer 26 is preferably transparent, in particular clear and transparent. The stabilization layer 26 preferably has a smooth surface.

[0123] One or more further layers which fulfil further functions may be located between the release layer 21 and the replication layer 23. For example, an optional protective layer 22 arranged between the release layer 21 and the replication layer 23 may be provided. This achieves in particular a stabilizing mechanical effect against degradation when the security element 20 is laminated, in particular when the security element 20 is laminated in the recording layer 11 and the cover layer 12 composed of polycarbonate. For this purpose, such a protective layer 22 is already thermally stable or preferably thermally stable, for example by radiation crosslinking or chemical crosslinking. The protective layer 22 here is formed, for example, on the basis of the following materials: thermoplastics and / or thermoplastic elastomers and / or crosslinked polymers, preferably UV crosslinked polymers, isocyanates, additives, catalysts, release agents.

[0124] The protective layer may also be transparent, in particular highly transparent, and / or have a low surface roughness, for example be smooth, in particular providing an R3z value of the protective layer of less than 2 μm, preferably less than 0.5 μm.

[0125] The relief surface of the replication layer 23 is preferably formed with an optically active structure. The relief surface has been molded into the replication layer 23 or has been molded into the replication layer 23 by replication. Molding can be achieved in a thermoplastic manner by the following process: the surface is structured into a relief under pressure and temperature by a tool with an optically active structure. The replication layer 23 can also be formed by a polymerizable varnish or a polymerized varnish, which is preferably composed of monomers and oligomers, which are polymerized or have been polymerized after or during the introduction of the relief. This polymerization can be achieved by UV irradiation or electron beam irradiation. The replication layer 23 can also be represented by a hybrid form that can be deformed by thermoplastically and then cured. The corresponding relief surface has been molded into the replication layer 23 or has been molded into the replication layer 23, in particular by a replication tool for thermal replication and / or UV replication. The surface relief can also be introduced by laser or has been introduced by laser. The replication layer 23 may also be a photosensitive layer, the relief surface being introduced by exposure to light by exposing the replication layer 23 to light having a pattern of different brightnesses and then washing away or dissolving, depending on the type of photosensitivity, the areas of the replication layer 23 that have been exposed to light or not, in particular by means of solvents.

[0126] Before replication, the replication layer 23 preferably has a smooth surface. As materials for the replication layer 23, it particularly comprises or consists of the following materials: thermoplastics, crosslinked polymers, preferably UV crosslinked polymers. UV crosslinked polymers are particularly cured by UV radiation with a wavelength of 100 nm to 400 nm. The replication layer 23 preferably comprises or preferably consists of a material selected from the following substances, alone or in combination: polyester, polyurethane, polyacrylate, ethylene-vinyl acetate copolymer resin, polymethyl methacrylate, epoxy resin, cellulose-based resin.

[0127] When the security element is laminated, the replication layer 23 preferably does not soften. In particular, the softening temperature of the replication layer 23 is higher than the lamination temperature of the lamination. As a result, the replication layer 23, in particular the structures molded into the replication layer 23, can remain stable during lamination. For example, here, the gloss of the decorative layer is preserved, for example by a relief surface molded therein, which ensures a particularly high level of anti-counterfeiting protection.

[0128] Preferably one of the following relief surfaces or a combination of two or more of the following relief surfaces is provided as the relief surface: a diffractive surface relief, a holographic surface relief, a first-order diffraction grating, a zero-order diffraction structure, a blazed grating, an achromatic surface relief, a surface relief in the form of lenses and / or lens grids, a micromirror arrangement, microprisms, microlenses, microfacets, a free surface, a mirror surface, a matte structure (in particular an isotropic or anisotropic matte structure).

[0129] The replication layer 23 here preferably has different partial regions and / or consists of different relief surfaces in the relief surface, in which different relief surfaces are molded, which relief surfaces differ in particular in one or more relief parameters. A plurality of relief surfaces listed above can also be superimposed on one another.

[0130] The thickness of the replication layer 23 is, for example, 8 μm, and may preferably be 0.2 μm to 20 μm, preferably 0.2 μm to 10 μm.

[0131] Before replication, the surface roughness of the replication layer is preferably very low, for example smooth. In particular, the R3z value of the replication layer surface is less than 2 μm, preferably less than 0.5 μm.

[0132] Figure 2a , 2b , 3a and 3b show a method for producing a laminate 1, which is in particular a security document. For example, a laminate can be produced, for example Figures 1a to 1d As shown, the laminate is particularly suitable for the test.

[0133] In the method, the following steps are performed, for example, in a specified order:

[0134] - preparing the recording layer 11;

[0135] - preparing a transparent cover layer 12;

[0136] - Preparing the security element 20 .

[0137] The security element comprises a release layer 21, a replication layer 23 having a relief surface arranged on its side facing away from the release layer 21, a reflection layer 24 arranged on the relief surface, and an adhesive layer 25 forming the side of the security element 20 facing away from the release layer 21.

[0138] like Figure 2a and Figure 2b As shown, the security element 20 has been applied to the cover layer 12 or applied to the cover layer 12, or as Figure 3a and Figure 3b As shown, it is attached to the recording layer 11. Thus, in particular the security element 20 is subsequently adhered to the cover layer 12 or the recording layer 11 using the adhesive layer 25.

[0139] Depending on which of the two layers 11 and 12 the security element 20 is or has been applied to, the preparation of the other layer can also be carried out only afterwards. The recording layer 11 and the cover layer 12 are then preferably arranged such that the security element 20 is arranged between these two layers.

[0140] Then, the security element 20 is laminated between the recording layer 11 and the cover layer 12. Figure 2a and 2b The adhesive layer 25 adheres to the cover layer 12 and the release layer 21 adheres to the recording layer 11. Figure 3a and 3b In the steps shown, the adhesive layer 25 is then adhered to the recording layer 11 and the release layer 21 is adhered to the cover layer 12. These two alternatives can optionally also be combined by using a plurality of security elements.

[0141] The adhesive layer 25 of the security element 20 is formed so as to be separable by tension applied to the security element 20 by the recording layer 11 and the cover layer 12 .

[0142] With regard to the specific design of the security element 20, particular reference is also made to the described embodiments of the security element of the laminate according to the invention.

[0143] For laminating the security element 20 , a lamination method is already carried out or preferably a lamination method is carried out, preferably by means of a roll laminator or a lifting and lowering press.

[0144] In the case of a roll laminator, the recording layer 11, the cover layer 12 and the security element 20 disposed between the two layers can be inserted between at least two heated rollers, for example. In the case of a lift press, the recording layer 11, the cover layer 12 and the security element 20 disposed between the two layers can be inserted between heating plates, for example.

[0145] The lamination has preferably already been carried out by applying a pressure of 10 N / cm2 to the recording layer 11, the cover layer 12 and / or the security element 20. 2 Up to 400N / cm 2 , preferably 40N / cm 2 Up to 200N / cm 2 or by applying a pressure of 10 N / cm2 to the recording layer 11, the cover layer 12 and / or the security element 20. 2 Up to 400N / cm 2 , preferably 40N / cm 2 Up to 200N / cm 2 The lamination can be achieved by a temperature of more than 150° C., preferably 160° C. to 210° C. or by a temperature of more than 150° C., preferably 160° C. to 210° C., which acts on the recording layer 11, the cover layer 12 and / or the security element 20 from a heat source, in particular from one or more heating rollers or one or more heating plates. The lamination is preferably carried out by a contact time of 1 minute or more and 30 minutes or less of the heat source with the recording layer 11 and / or the cover layer 12 or by a contact time of 1 minute or more and 30 minutes or less of the heat source with the recording layer 11 and / or the cover layer 12. The contact of the heat source with the recording layer 11 and the cover layer 12 is preferably achieved directly or indirectly via other layers. The above-mentioned settings are preferably used for the cover layer 12 and the recording layer 11 composed of or containing polycarbonate. For other materials, such as polyvinyl chloride, different temperature and pressure settings can be used that are matched to the material to be processed.

[0146] Figure 4a The transfer film and the production of the transfer film are shown. Figure 4b A further embodiment of a transfer film and its production is shown. The transfer film can be used to attach the security element 20 to the cover layer 12 or the recording layer 11 .

[0147] like Figure 2a , 2b , 3a and 3b, before preparing the anti-counterfeiting element 20 (the cover layer 12 or the recording layer 11 is provided with the anti-counterfeiting element 20) or when preparing the anti-counterfeiting element 20 (the cover layer 12 or the recording layer 11 is provided with the anti-counterfeiting element 20), the following steps can be performed in a specified order:

[0148] -like Figure 4a Or as shown in 4b, a transfer film having a carrier layer 31 and a transfer layer is prepared, wherein the transfer layer has the security element 20, and the release layer 21 is arranged on a side of the security element 20 facing the carrier layer 31;

[0149] The security element 20 is applied to the recording layer 11 or the covering layer 12 .

[0150] A mechanically stable, and therefore in particular self-supporting, carrier film 31 is conveniently used as carrier layer 31. Typically, the carrier layer comprises or consists of polyester, preferably polyethylene terephthalate (abbreviation: PET) or polyethylene naphthalate (abbreviation: PEN). The thickness of the carrier layer is preferably 5 to 150 μm, preferably 5 to 50 μm, further preferably 10 to 25 μm. The carrier layer is preferably transparent.

[0151] The security element 20 is applied, for example, by the following steps, in particular in the specified order:

[0152] - applying an adhesive layer 25 to the recording layer 11 or the cover layer 12;

[0153] The carrier layer 31 is peeled off from the transfer layer, with the result that the security element 20 remains on the recording layer 11 or the cover layer 12 .

[0154] The transfer layer can be transferred completely or in areas, for example in a pattern predefined by an embossing die or an embossing roller. Alternatively, an adhesive printed on an area, in particular a patterned adhesive, can transfer the transfer layer in this area, with the result that the security element is formed by the printed adhesive and the transfer layer transferred in this area, for example without an adhesive layer or with an adhesive layer, preferably as an adhesion promoter layer, which is supplemented by the printed adhesive layer. The adhesive layer 25 of the security element 20 then preferably comprises or consists of the printed adhesive layer.

[0155] The application of the adhesive layer 25 to the recording layer 11 or the cover layer 12 is preferably carried out by hot stamping or by hot stamping. Hot stamping can be carried out at a temperature of 80° C. to 300° C., preferably 100° C. to 240° C., particularly preferably 100° C. to 180° C. Hot stamping is preferably carried out at a pressure of 10 N / cm 2 Up to 10,000N / cm 2 , preferably 100N / cm 2 Up to 5000N / cm 2 The punching pressure is 10N / cm 2 Up to 10,000N / cm 2 , preferably 100N / cm 2 Up to 5000N / cm 2 The hot stamping is preferably carried out with a stamping time of 0.01 s to 2 s, preferably 0.01 s to 1 s or with a stamping time of 0.01 s to 2 s, preferably 0.01 s to 1 s.

[0156] like Figure 4aAs shown, the transfer film can be produced by applying an optional wax layer 32 , a release layer 21 , an optional protective layer 22 and a replication layer 23 successively to a carrier layer 31 .

[0157] During application, the release layer 21 conveniently ensures that the composite layer of the transfer layer can be detached from the carrier layer 31. When laminated into the laminate 1, this layer additionally ensures that good adhesion to the adjacent cover layer 12 or recording layer 11 is achieved, in particular if these contain polycarbonate or consist of polycarbonate. Figure 4a and Figure 4b The optional wax layer 32 shown can be arranged between the release layer 21 and the carrier layer 31. Particularly, the separation of the transfer layer and the carrier can be improved by one or more wax layers (preferably thin). In various cases, the thickness of the wax layer is preferably 1nm to 50nm. Preferably, the wax layer 32 is removed before the anti-counterfeiting element is laminated. Particularly, the firm connection of the release layer and the recording layer or the cover layer can be realized thus.

[0158] Once the replication layer 23 has been applied, the relief surface can be molded into the replication layer 23 by replication, as described above. The reflective layer 24 can then be applied to the relief surface, in particular over the entire surface, or also to parts or areas of the surface, for example in the form of a pattern. For this purpose, the reflective layer is, for example, vapor deposited or sputtered in a vacuum. Figure 4b As shown, the optional stabilization layer 26 or Figure 4a The adhesive layer 25 shown can preferably be applied directly to the reflective layer 24, especially if the reflective layer 24 is deposited on a portion of the surface; it can also be applied to the replication layer 23. Figure 4b As shown, in this case, before the adhesive layer 25 is subsequently applied to the stabilization layer 26 , an optional stabilization layer 26 can additionally be applied between the adhesive layer 25 and the reflective layer 24 , in particular between the adhesive layer 25 and the replication layer 23 .

[0159] The adhesive layer 25 may also consist of a plurality of layers. For example, the adhesive layer 25 may comprise, in particular in addition to the ductile layer, one or more adhesion promoter layers to ensure bonding of the adhesive layer 25 to the reflective layer 24 or to the optionally present stabilizing layer 26. The layer of the adhesive layer 25 which is adhered to the cover layer 12 or the recording layer 11 in the laminate 1 may be applied in particular as a hot glue layer of the transfer layer or as a cold glue layer to the transfer layer in a later step and, where appropriate, to an already existing layer of the adhesive layer 25 or to the recording layer 11 or the cover layer 12.

[0160] Figure 5 The setup for a peel test is shown, for example as described above, in particular according to ISO / IEC

[0161] 10373-1:2006(E); test in paragraph 5.3.

[0162] In particular, in the peel test, the optional pre-treated card is cut into 10 mm wide test strips. For example, Figure 5 This test strip of laminate 1 is shown schematically in cross section.

[0163] For example, all layers on one side of the security element 20 are removed, preferably with a length of 5 mm to 10 mm. The security element 20 is particularly The cover layer 12 is stripped off the core, ie in particular the recording layer 11, for example using a sharp knife. The stripping is expediently only carried out partially.

[0164] The torn end is then preferably fixed to the support of the tensile tester by means of a fixing clip or adhesive tape 40. Preferably, a right angle is created between the tearing layer (especially the cover layer 12) fixed to the tensile tester and the untorn layer (especially the corresponding part in the cover layer 12, the recording layer 11 and the security element 20). In particular, a right angle is created between the cover layer 12 and the recording layer 11. The bottom of the laminate 1 or its test strip, especially the recording layer 11, can be conveniently fixed on a stabilizing plate. During the tensile measurement, the detached film layer can be guided to a roller. The adhesion (peel strength) is preferably plotted on a graph and then evaluated, wherein the first 5 mm and the last 5 mm of the measurement are preferably not taken into account. For example, the result is given in N / 10 mm.

[0165] Measurements can also be carried out in locations without security elements, for example in order to test the adhesion between cover layer and recording layer.

[0166] The influence of the different layers of the laminate 1 on the peeling force can advantageously be determined by a peeling force test. The main influence on the peeling force is the dissipation of the adhesive, wherein the energy is converted to cohesive failure. If the structure delaminates due to adhesive failure, in particular at the boundary surface between the adhesive layer 25 and the cover layer 12 or the recording layer 11, the resulting peeling force is much lower than in the case of cohesive failure. Advantageously, a peeling force for detaching the cover layer 12 can be set that is equal to or greater than 3.5 N / 10 mm strip width.

[0167] The elastic modulus can be measured in particular as follows: The elastic modulus is determined in accordance with DIN EN ISO 527-3: 2003-07 ("Plastics - Determination of tensile properties - Part 3: Test conditions for films and sheets - Issue date: 2003-07"), preferably at room temperature (25°C). The tensile elastic modulus is measured by means of a tensile testing machine (e.g. from the ZwickRoell Group in Ulm, Germany). GmbH & Co. KG, Ulm, DE.) on a film test strip. The width of the film strip is preferably 15 mm + / - 0.1 mm, and for film materials with high elongation, the length of the film strip is preferably 100 mm + / - 0.5 mm or 50 mm + / - 0.5 mm. For a film length of 100 mm, the test speed is 10 mm / min + / - 1 mm / min, or for a film length of 50 mm, the test speed is 5 mm / min + / - 1 mm / min.

[0168] Figure 6 The development of a ductile material failure 6 and of a brittle material failure 5 are shown by way of example in a force versus displacement diagram. In the force versus displacement diagram, the y-axis represents the force F and the x-axis represents the displacement L. A brittle material failure 5 is characterized in this respect by the fact that the measured force rises sharply and then drops abruptly once the tensile strength of the material is reached. In the case of a ductile material failure 6, on the other hand, the rise of the measured curve proves to be significantly less steep, wherein once the yield stress is reached, the force remains at an essentially constant level. This material behavior is also particularly evident in the results of the peeling test. When the cover layer is peeled off, the dissipation in the region of the fracture tip or crack tip remains at the highest possible level, especially in the case of cohesive failures, which is not the case with adhesive failures.

[0169] Exemplary experimental and control tests used for the examination are described below.

[0170] For verification purposes, a corresponding pattern was produced, for example. In particular, a hot stamping film with a thickness of 19 μm was used as a basis (B944059, produced by Leonhard Kurz Stiftung & Co. KG, Fürth, Germany). The film had the following structure: PET carrier, release layer, protective layer and replication layer. The relief surface was molded into the replication layer, wherein a cylindrical metal plate was pressed against the replication layer. The temperature of the plate was 180°C and the pressure was 100 N / cm 2 , the production speed is 20 meters / minute.

[0171] A reflective layer consisting of zinc sulfite (ZnS) with a thickness of 60 nm was then applied to the relief surface by vacuum coating. In a gravure printing method, a binder based on polymethyl methacrylate was then applied, wherein the binder layer was varied with respect to the layer thickness investigated. After removal of the solvent, the following layer thicknesses could be determined: 1 μm, 4 μm and 6 μm.

[0172] The security element was then applied to a transparent cover layer of polycarbonate (Makrofol ID 6-2, produced by Covestro AG, Leverkusen, DE) with a thickness of 100 μm or a transparent recording layer of polycarbonate (Makrofol ID 6-2 laserable, produced by Covestro) with a thickness of 100 μm. A hot stamping transfer machine was used for this purpose, wherein a stamping temperature of 170° C. and a force of 250 N / cm 2 of punching pressure and a punching time of 0.5 seconds. Subsequently, cards with a structure in accordance with ISO / IEC 7810:2003(E) were produced, whereby white polycarbonate (Makrofol ID 6-4, produced by Covestro) with a thickness of 100 μm was used for the remainder of the card structure. For the patterns of experimental series 1, the adhesive layer of the security element formed an adhesive connection with the covering layer; for the patterns of experimental series 2, the adhesive layer of the security element formed a connection with the recording layer. A processing temperature of 190°C and a pressure of 120 N / cm 2 The pressing pressure was 100 and the pressing time was 15 minutes. Subsequently, the cards were punched out of the laminate.

[0173] The results of Experimental Series 1 show the peel forces with respect to the recording layer and the security element. The results of Experimental Series 2 show the peel forces with respect to the cover layer and the security element. The peel forces are determined by a peel test, which is carried out according to ISO / IEC 10373-1:2006 (E); paragraph 5.3 and / or the above-mentioned peel test.

[0174] The results of these measurements can be found in Table 1.

[0175]

[0176] Table 1

[0177] As shown in Table 1, the adhesive thickness in experimental series 1 has an influence on the peel force. The peel force increases with increasing layer thickness. In the case of a layer thickness of 1 μm, the peel force is 0.8 N / 10 mm sample width, which is caused by the adhesion failure between the adhesive layer and the recording layer of the security element. On the other hand, an increase in the layer thickness to 4 μm leads to a cohesive failure, which in turn indicates an increase in the peel force to 2.6 N / 10 mm sample width. An increase in the layer thickness to 6 μm leads to an increase in the peel force to 3.9 N / 10 mm sample width, which in turn leads to a cohesive failure of the adhesive. This behavior can also be observed in experimental series 2. Again, in the case of a layer thickness of 1 μm, the peel force is as low as 0.7 N / 10 mm, where adhesion failure occurs between the adhesive layer and the cover layer. An increase in the layer thickness to 4 μm leads to a cohesive failure of the adhesive, which is evidenced by an increase in the peel force to 2.4 N / 10 mm sample width. In the case of a layer thickness of 6 μm, cohesive failure also occurs, and the peel force increases to 4.9 N / 10 mm sample width. In particular, for different laminate structures, the separable adhesive layer can also be determined accordingly.

[0178] In the comparison of experimental series 1 and 2, the following points can be determined in particular:

[0179] - The bonding of the adhesive layer to the cover layer and the recording layer can produce considerable peel forces.

[0180] - In the case of an adhesive layer thickness of 1 μm, both structures show adhesive failure, which may transition to cohesive failure from a 4 μm layer thickness.

[0181] In the case of both test series, for an adhesive layer with a layer thickness of 6 μm, a peel force of at least 3.5 N / 10 mm specimen width could be achieved in each case.

[0182] In the case of a peel test, the alignment of the security element in the layer structure of the security document may have no influence on the fracture behavior in the adhesive layer of the security element.

[0183] - In order to achieve a peel force of at least 3.5 N / 10 mm test specimen width, for example, separation of the adhesive layer may not occur as a purely cohesive failure. Under defined conditions, in particular according to the standard

[0184] ISO / IEC 10373-1:2006(E); paragraph 5.3, Temporary changes in peel force, such as a temporary drop or rise in peel force, which can typically be observed during the transition from cohesive failure to adhesive failure, may be ignored.

[0185] Figure 7Schematically shows an exemplary crack growth in a section of a laminate having an adhesive layer 25 and a layer 1112 directly adjacent to the adhesive layer 25. The layer 1112 is either the cover layer 11 or the recording layer 12. Therefore, the adhesive layer 25 and the layer 1112 particularly have a boundary surface formed between these layers or as a contact surface of the two layers. Figure 7 The broken lines in show the cracks 51 and 52. In the case of a peel test and / or an attempt to detach the cover layer 11 and / or the recording layer 12, in particular the layer 1112 shown, for example, one of the two cracks 51 and 52 may be generated.

[0186] As shown by crack 51, it is particularly likely that during cohesive failure the crack tip temporarily strikes the boundary surface between adhesive layer 25 and layer 1112 directly adjacent to the adhesive layer, but in the case of sustained separation the crack tip does not extend along this boundary surface.

[0187] As shown in particular with reference to crack 52, the laminate can be designed such that the adhesive layer 25 detaches at one or more partial surfaces (here in region 520) at the boundary surface with the directly adjacent layer 1112, for example in the event of an adhesive failure. However, the surface area of ​​these one or more partial surfaces in region 520 is advantageously smaller than the remaining surface of the boundary surface, in particular resulting in a peel force of at least 3.5 N / 10 mm. Here, as an example, for crack 52, the remaining surface is present in region 521. In region 521, the remaining surface of the boundary surface particularly has remnants of the adhesive layer 25, since cohesive failure occurs there. When a line perpendicular to the plane spanned by the boundary surface (thus, for example in Figure 7 The surface area is particularly determined when viewed from bottom to top.

[0188] For example, the remaining surface present in region 521 in particular covers at least 50%, preferably at least 80%, preferably at least 90% of the surface area of ​​the boundary surface and / or the partial surface present in, for example, region 520 covers less than 50%, preferably less than 20%, preferably less than 10% of the surface area of ​​the boundary surface.

[0189] Advantageously, in the presence of irregularities in the laminate, this can lead to local peaks in tensile stress when the layer 1112 is detached, thus leading to local adhesive failures and thus also to major cohesive failures, with the result that an overall high peel force is still ensured. This is also possible with relatively thin adhesive layers with a layer thickness of at least 3.5 μm.

[0190] Therefore, in a preferred embodiment, the thickness of the adhesive layer is advantageously at least 3.5 μm or more, preferably at least 4 μm or more, and in particular at least 6 μm or more.

[0191] Figure Number

[0192] 1 Laminated materials

[0193] 11 Overlay

[0194] 12 Recording Layer

[0195] 1112 Layer directly adjacent to adhesive layer 20 Anti-counterfeiting elements

[0196] 21 Detachment layer

[0197] 22 Protective layer

[0198] 23 Duplicate Layer

[0199] 24 Reflection layer

[0200] 25 Adhesive layer

[0201] 26 Stable Layer

[0202] 31 Carrier film

[0203] 32 Wax layer

[0204] 40 Clips or tape

[0205] r Radius

[0206] α Angle

[0207] x The length of the tear-off layer

[0208] L Displacement

[0209] F-Force

[0210] 5 Failure of brittle materials

[0211] 6 Ductile Material Failure

[0212] 51,52 Crack

[0213] 510 Region with partial surface

[0214] 520 Area with remaining surface

Claims

1. A laminated material (1), in particular a security document, include: A recording layer (11), a transparent cover layer (12) and a security element (20) laminated between the recording layer (11) and the cover layer (12), wherein the security element (20) comprises a release layer (21), a replication layer (21) having a relief surface arranged on its side facing away from the release layer (21), a reflection layer (24) arranged on the relief surface and an adhesive layer (25) forming the side of the security element (20) facing away from the release layer (21), wherein: a) the adhesive layer (25) adheres to the recording layer (11) and the release layer (21) adheres to the cover layer (12), or the adhesive layer (25) adheres to the cover layer (12) and the release layer (21) adheres to the recording layer (11), and b) The laminate (1) is designed so that the adhesive layer (25) of the security element (20) can be separated by the tension exerted on the security element (20) by the recording layer (11) and the cover layer (12).

2. The laminate according to claim 1, Features: The adhesive layer (25) has the lowest elastic modulus and the lowest yield point, in particular the upper yield point, of the layers of the security element.

3. The laminate material according to claim 1 or 2, Features: The adhesive force of the adhesive layer (25) to its directly adjacent layer consisting of the cover layer (12) or the recording layer (11) is higher than the cohesive force of the adhesive layer (25).

4. A laminate material as claimed in any one of the preceding claims, Features: The peel force for detaching the covering layer (12), preferably the peel force for separating the covering layer (12) from the security element (20), in particular the peel force measured by a peel test, preferably the peel force measured by a peel test with a peel angle (α) of 90°, is equal to or greater than 3.5 N / 10 mm strip width.

5. A laminate material as claimed in any one of the preceding claims, Features: Adhesion within the adhesive layer (25), in particular the cohesion of the adhesive layer (25) - lower than the adhesion between the security element (20) and the recording layer (11) (11), and also - lower than the adhesion between the security element (20) and the covering layer (12) (12).

6. A laminate material as claimed in any one of the preceding claims, Features: Of the cohesive force and the adhesive force within the security element (20) or within the laminate (1) having the security element, the smallest force is the cohesive force of the adhesive layer (25).

7. A laminate material as claimed in any one of the preceding claims, Features: The adhesive layer (25) comprises an ductile layer or consists of an ductile layer, wherein the ductile layer is in particular the layer of the security element (20) having the greatest elongation at break.

8. A laminate material as claimed in any one of the preceding claims, Features: The adhesive layer (25), in particular the spreading layer, consists of a material having an elastic modulus of 20 MPa to 300 MPa, preferably 50 MPa to 200 MPa, preferably 75 MPa to 150 MPa.

9. A laminate material as claimed in any one of the preceding claims, Features: The layer thickness of the adhesive layer ( 25 ) is 0.2 μm to 20 μm, preferably 0.2 μm to 10 μm and / or preferably 3.5 μm to 20 μm, further preferably 3.5 μm to 10 μm and / or 6 μm to 20 μm, in particular 6 μm to 10 μm.

10. A laminate material as claimed in any one of the preceding claims, Features: The adhesive layer ( 25 ) comprises a thermoplastic or a polymer to be or to be crosslinked, in particular polymethyl methacrylate and / or butyl methacrylate.

11. A laminate material as claimed in any one of the preceding claims, Features: The adhesive layer (25) is translucent and / or contains one or more additives selected from fillers, such as TiO 2 ,BaSO 4 or silica.

12. A laminate material as claimed in any one of the preceding claims, Features: The thickness of the release layer (21) is 0.2 μm to 10 μm, preferably 0.2 μm to 5 μm.

13. A laminate material as claimed in any one of the preceding claims, Features: The release layer (21) comprises or consists of a thermoplastic, a thermoplastic elastomer or a cross-linked polymer or a UV cross-linked polymer.

14. A laminate material as claimed in any one of the preceding claims, Features: The relief surface of the replication layer (23) forms an optically active structure.

15. A laminate material as claimed in any one of the preceding claims, Features: The replication layer ( 23 ) comprises or consists of a thermoplastic or a cross-linked polymer or a UV-cross-linked polymer.

16. A laminate material as claimed in any one of the preceding claims, Features: The thickness of the replication layer (23) is 0.2 μm to 20 μm, preferably 0.2 μm to 10 μm.

17. A laminate material as claimed in any one of the preceding claims, Features: The reflective layer (24) comprises a metal layer or a high refractive index layer or a combination thereof, or consists of a metal layer or a high refractive index layer or a combination thereof.

18. A laminate material as claimed in any one of the preceding claims, Features: For wavelengths between 420 nm and 780 nm, the reflective layer (24) has a refractive index greater than 1.

9.

19. A laminate material as claimed in any one of the preceding claims, Features: The layer thickness of the reflective layer (24) is 40 nm to 200 nm, preferably 40 nm to 100 nm.

20. A laminate material as claimed in any one of the preceding claims, It is characterized in that On the side of the adhesive layer ( 25 ) facing the replication layer ( 23 ) and the reflective layer ( 24 ), the security element ( 20 ) has a stabilization layer ( 26 ).

21. A laminate material as claimed in any one of the preceding claims, Features: The thickness of the stabilizing layer (26) is 0.5 μm to 20 μm, preferably 1 μm to 10 μm.

22. A laminate material as claimed in any one of the preceding claims, It is characterized in that In particular, if the adhesive layer (25) is adhered to the recording layer (11), the ratio of the thickness of the adhesive layer (25) to the thickness of the stabilizing layer (26) is 0.4 to 4.

23. A laminate material as claimed in any one of the preceding claims, Features: The stabilization layer (26) comprises or consists of a layer consisting of a material having an elastic modulus of 500 MPa to 1500 MPa.

24. A laminate material as claimed in any one of the preceding claims, Features: The stabilization layer ( 26 ) comprises or consists of a thermoplastic, a thermoplastic elastomer or a cross-linked polymer, preferably a UV-cross-linked polymer.

25. A laminate material as claimed in any one of the preceding claims, Features: The recording layer (11) and the cover layer (12) contain polycarbonate or consist of polycarbonate.

26. A laminate material as claimed in any one of the preceding claims, Features: The layer thickness of the cover layer (12) satisfies one or a combination of the following conditions: the layer thickness of the cover layer (12) is 1.25 to 250 relative to the layer thickness of the adhesive layer (25); the sum of the thickness of the adhesive layer and the cover layer is 26 μm to 270 μm; The layer thickness of the cover layer (12) is 25 μm to 250 μm.

27. A laminate material as claimed in any one of the preceding claims, Features: The recording layer (11) has a thickness of 25 μm to 250 μm.

28. A laminate material as claimed in any one of the preceding claims, Features: The adhesive layer (25) is adhered to the cover layer (12) or the recording layer (11) by an adhesive connection.

29. A laminate material as claimed in any one of the preceding claims, Features: The release layer (21) is adhered to the cover layer (12) or the recording layer (11) by means of a welded connection.

30. A laminate material as claimed in any one of the preceding claims, Features: The adhesive layer (25) is adhered to the reflective layer (24) by a material bonding connection and / or to the replication layer (23) by a material bonding connection.

31. A method for producing a laminated material, in particular a security document, as claimed in any one of the preceding claims, comprising the following steps, in particular in a specified order: - preparing a recording layer (11); - preparing a covering layer (12); - producing a security element (20), in particular a security element (20) as claimed in any one of the preceding claims, in, The security element (20) comprises a release layer (21), a replication layer (23), a reflection layer (24) and an adhesive layer (25), wherein the replication layer (23) has a relief surface arranged on its side facing away from the release layer (21), the reflection layer (24) is arranged on the relief surface, the adhesive layer (25) forms the side of the security element (20) facing away from the release layer (21), and the security element (20) is adhered to the cover layer (12) or the recording layer (11) via the adhesive layer (25) or has been adhered to the cover layer (12) or the recording layer (11) via the adhesive layer (25); - laminating the security element (20) between the recording layer (11) and the cover layer (12) such that: a) the adhesive layer (25) adheres to the recording layer (11) and the release layer (21) adheres to the cover layer (12), or the adhesive layer (25) adheres to the cover layer (12) and the release layer (21) adheres to the recording layer (11), and b) The adhesive layer (25) of the security element (20) can be separated by the tension exerted on the security element (20) by the recording layer (11) and the cover layer (12).

32. The method of claim 31, It is characterized in that For laminating the security element (20), the lamination process is carried out by means of a roll laminator or a lifting and lowering press.

33. The method of claim 31 or 32, Features: The lamination is performed by applying a pressure of 10 N / cm2 on the recording layer (11), the cover layer (12) and / or the security element (20). 2 Up to 400N / cm 2 , preferably 40N / cm 2 Up to 200N / cm 2 pressure to achieve.

34. The method of any one of claims 31 to 33, Features: Lamination is achieved by temperatures exceeding 150° C., preferably 160° C. to 210° C., which are applied to the recording layer ( 11 ), the cover layer ( 12 ) and / or the security element by a heat source, in particular one or more heated rollers or one or more heated plates.

35. The method of any one of claims 31 to 34, Features: The lamination is performed by contacting the heat source with the recording layer (11) and / or the cover layer (12) for a time of 1 minute or more and 30 minutes or less.

36. The method of any one of claims 31 to 35, Features: Before or in order to prepare a cover layer (12) or a recording layer (11) having a security element (20), the following steps are performed in a specified order: - preparing a transfer film having a carrier layer (31) and a transfer layer, wherein the transfer layer has the security element (20), and the release layer (21) is arranged on a side of the security element (20) facing the carrier layer; - Applying the security element (20) to the recording layer (11) or the covering layer (12).

37. The method of any one of claims 31 to 36, Features: The application of the security element (20) is carried out by the following steps in the specified order: - applying an adhesive layer to the recording layer (11) or the cover layer (12); The carrier layer (31) is peeled off from the transfer layer, with the result that the security element remains on the recording layer (11) or the cover layer (12).

38. The method of any one of claims 31 to 37, Features: The adhesive layer (25) is applied by hot stamping.

39. The method of any one of claims 31 to 38, Features: Hot stamping is performed at a temperature of 80°C to 300°C, preferably 100°C to 240°C, particularly preferably 100°C to 180°C.

40. The method of any one of claims 31 to 39, Features: Hot stamping at 10N / cm 2 Up to 10000N / cm 2 , preferably 100N / cm 2 Up to 5000N / cm 2 The stamping pressure is high.

41. The method of any one of claims 31 to 40, Features: The hot stamping is performed with a stamping time of 0.01 s to 2 s, preferably 0.01 s to 1 s.

Citation Information

Patent Citations

  • Multilayer volume hologram, and label for multilayer volume hologram fabrication

    EP1168111A2

  • Interlaminar sandwich with diffraction structure

    US5104471A

  • Image-receiving element for thermal dye transfer method

    US5380695A

  • Volume hologram laminate and label for preparing volume hologram laminate

    US6066378A